The Impact of Agricultural Exports on Brazil's Economic Growth: A Sectoral Analysis - Miguel, Carlos (Raudhah Publisher, 2024)
Agricultural exports have long been a vital component of Brazil's economic structure, influencing the nation's overall economic performance. This study explores the impact of agricultural exports on Brazil's economic growth, focusing on sectoral contributions and identifying the dynamics within various agricultural sub-sectors. The primary issue addressed is how these exports contribute to economic growth and the extent to which different sectors within agriculture drive this growth. The research aims to analyze the relationship between agricultural exports and economic growth in Brazil by investigating specific sectors that significantly contribute to the nation's economy. A qualitative research methodology is employed, utilizing data from government reports, economic analyses, and academic literature to gain insights into the economic impacts of agricultural exports. The study involves a sectoral analysis to identify the most influential agricultural products in driving economic growth and examines how fluctuations in global demand and pricing affect these sectors. The findings reveal that certain agricultural sectors, such as soybeans and sugar, play a crucial role in Brazil's economic growth. However, the reliance on these exports also exposes the economy to risks associated with global market volatility. The results underscore the need for Brazil to diversify its agricultural exports and strengthen its domestic agricultural policies to enhance economic stability.